Diseminasi Dampak Pencemaran Lingkungan Bagi Kesehatan Di SDN SUKABUMI 2 KOTA PROBOLINGGO - ., Ani Anjarwati; ., Vita Rahmatun Nazillah; ., Moh. Umar Alfaruqi; ., Nur Aulia Wijaya; ., Violitha Volvariella Volvacea; ., Ika Setyawati (CV. ITTC INDONESIA, 2022)
Environmental pollution in the technological era has now reached an alarming level. This is indicated by the large number of pollutant substances produced from daily life activities. Starting from the many industrial factories, factory waste, and motorized vehicles to make pollution. As a source of problems in the survival of humans and living things. The environment that is polluted by polluting substances not only affects human health, but all living things and the environment will get the impact of environmental pollution. Causing infectious and even dangerous diseases is a health disorder that can cause death. Environmental pollution can be seen directly and indirectly, some smell and don't smell. Ordinary people who do not understand the importance of maintaining a clean environment and the impact that will be caused by environmental pollution. In the process of environmental pollution to ordinary people, it can be done by giving examples directly and indirectly. Directly as an example of air pollution when pollution smoke comes out of factory chimneys. And indirectly through artificial simulation or modeling by looking at the distribution of pollution.